Quick Reference Guide: Introduced Constrictors in Florida - Steve A. Johnson; Monica E. McGarrity (EDIS)
WEC302, a 2-page fact sheet by Steve A. Johnson and Monica E. McGarrity, is a quick reference guide to identification of the constrictors one is most likely to encounter in Florida. Published by the UF Department of Wildlife Ecology and Conservation, November 2010.